Strengthening the Profile of Madrasah Ibtidaiyah Students in Harmonising Pancasila and Rahmatan Lil Alamin Values - Fadilah, Yulina; Soliha, Imro Atus (Electronic Journal of Education, Social Economics and Technology, 2024)
Students Profile of Pancasila and Profiles of Students of Rahmatan Lil Alamin can increasingly strengthen the Student Profile especially in Madrasah Ibtidaiyah. With the various values and dimensions contained in the two profiles, then can form the character of a student. This research uses a qualitative approach to library study methods. This research methodology involves systematic measures to gather, evaluate, and analyse written sources relevant to the focus of research. Library studies, as an important early stage in the research process, enable researchers to understand existing perspectives, to evaluate previous findings, and to build a solid foundation for research to be undertaken. The harmonization of the values of Pancasila and Rahmatan Lil Alamin can be realized by designing P5P2RA in both Intra-Curricular, Co-curricular and Extra-Courricular activities. In intra-curricular activities activities should be integrated with the substance of the lesson according to the themes defined. And in extracurricular activities, his activities are combined in the development of talent interests. A good integration between these three types of activities ensures that education not only focuses on academic achievement purely, but also on character development, skills, and potential holistically. Thus, students can experience learning that is diverse, interesting, and relevant to their needs, thus being able to be qualified individuals and ready to face the challenges of the future.